INITIAL OUTCOMES OF UNICOMPARTMENTAL KNEE ARTHROPLASTY IN PATIENTS WITH ISOLATED MEDIAL COMPARTMENT KNEE OSTEOARTHRITIS AT UNIVERSITY MEDICAL CENTER HO CHI MINH CITY (Vietnam Journal of Community Medicine, 2026)
Objectives: To evaluate the initial outcomes of unicompartmental knee arthroplasty in patients with isolated medial compartment knee osteoarthritis at University Medical Center Ho Chi Minh City.Methods: A retrospective case series was conducted on 18 patients who underwent cemented unicompartmental knee arthroplasty between 2018 and 2023. Outcome measures included pain intensity using the VAS, knee range of motion, knee score, knee function score, and lower limb alignment assessed by hip-knee-ankle angle using EOS imaging before and after surgery.Results: The mean age was 60.63 ± 6.25 years, with females accounting for 94.4% of patients. The mean follow-up duration was 3.9 years. The mean VAS score significantly decreased from 4.74 preoperatively to 1.11 postoperatively (p < 0.05). Knee flexion improved from 119.74135.4 degrees to 135.42 degrees (p < 0.05). The mean knee score increased from 67.26 to 89.00, and the mean knee function score from 72.37 to 86.32 (p < 0.05). Lower limb alignment was corrected toward a more physiological axis. No major complications were recorded during follow-up.Conclusions: Unicompartmental knee arthroplasty provided significant improvements in pain relief, knee function, and range of motion at mid-term follow-up in appropriately selected patients with isolated medial compartment knee osteoarthritis.
Keywords: Unicompartmental knee arthroplasty, knee osteoarthritis, partial knee replacement, medial compartment knee osteoarthritis.